2008
DOI: 10.1002/ejsp.573
|View full text |Cite
|
Sign up to set email alerts
|

When scowling may be a good thing: The influence of anger expressions on credibility

Abstract: Emotion displays do not only signal emotions but also have social signal value. A study was conducted to test the hypothesis that expressing anger when complaining may lead to positive outcomes for the complainant because anger signals goal obstruction and hence the presence of real harm. The results suggest that the social signal value of anger enhances the credibility of the complainant and hence leads to better compensation, but only when the complaint itself presents room for doubt. For highly justified co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…With regard to perceived feedback negativity, on receiving someone's negative feedback with liking emoticons, the recipient is likely to infer that the feedback provider still appreciates the individual's performance (Hareli et al, 2009;Van Kleef, De Dreu, & Manstead, 2006). The liking emoticons can strengthen the cognitions conveyed in the specific feedback that, despite some drawbacks in the task performance, the weaknesses are not very severe and there is still chance for improvement.…”
Section: Effects Of Liking Emoticons Vs No Emoticonmentioning
confidence: 99%
“…With regard to perceived feedback negativity, on receiving someone's negative feedback with liking emoticons, the recipient is likely to infer that the feedback provider still appreciates the individual's performance (Hareli et al, 2009;Van Kleef, De Dreu, & Manstead, 2006). The liking emoticons can strengthen the cognitions conveyed in the specific feedback that, despite some drawbacks in the task performance, the weaknesses are not very severe and there is still chance for improvement.…”
Section: Effects Of Liking Emoticons Vs No Emoticonmentioning
confidence: 99%
“…Thus, Knutson (1996) as well as Hess, Blairy and Kleck (2000) found that perceived high dominance and affiliation were associated with happiness expressions, high dominance and low affiliation were associated with anger and disgust expressions, and low dominance was associated with sadness and fear expressions. Other characteristics that can be inferred from facial expressive reactions include status (Tiedens, 2001) and credibility (Hareli et al, 2009). …”
Section: Emotion Expressions and Behavior Tendenciesmentioning
confidence: 99%
“…How do these two cues combine to determine perceptions of competence? Emotions may affect competence inferences only when other, more direct, information concerning competence—such as professional status—is absent or ambiguous. Previous research shows that emotions affect perceivers' judgements only when other relevant information is weak (see e.g., Hareli et al, 2009). Yet emotions can still affect perceptions of competence in spite of observers having other information indicating the target's competence level.…”
mentioning
confidence: 97%